Pemanfaatan Embung sebagai Sumber Air pada Subak Balangan dan Uma Tegal dalam Menghadapi Krisis Air - I Gusti Agung Putu Eryani; Made Widya Jayantari; Ni Made Ayu Gemuh Rasa Astiti (Universitas Sebelas Maret, 2025)
Utilization of Reservoirs as Water Sources in Subak Balangan and Uma Tegal in Response to Water Crisis. The water crisis is a major challenge in various regions of Indonesia, including Bali, which relies on traditional irrigation systems like Subak. This study highlights the water shortage issues in Subak Balangan and Uma Tegal, Desa Kuwum, Badung, Bali, driven by climate change and water use conflicts between upstream and downstream areas. These problems are exacerbated by inadequate irrigation channels, resulting in an inability to retain water during the rainy season and droughts in the dry season. Implementing water reservoirs is proposed as an effective solution. Reservoirs function as rainwater reservoirs that can be used during the dry season, ensuring year-round water availability and enhancing agricultural productivity. The study also involves the installation of geomembranes for the reservoir to improve water storage efficiency. The results show that reservoirs can stabilize the water supply for irrigation, reduce flood risks, and provide significant ecological and economic benefits for the farming community. Wise reservoir management, including water quality monitoring, environmental impact mitigation, and active community participation, is crucial for sustainable water availability. This study concludes that a reservoir is a sustainable solution for addressing the water crisis, optimizing water resource use, and supporting the economic well-being of local communities